Molecular and Bacteriological Detection of Some Bacterial Vaginosis Associate Bacteria in Women - Abed, Khawlah Abdulameer; Kandala, Nuha Joseph (Iraqi Journal of Science, 2022)
Bacterial vaginosis (BV) is one of the most common genital infections among women in the childbearing age. Many novel, fastidious and uncultivated bacterial species are related with BV. These are called bacterial vaginosis associated bacteria (BVAB), present in trace amount and have a significant role in the infection. A total of 80 vaginal swabs were obtained from 80 pregnant and non-pregnant women. Samples were collected from different hospitals in Baghdad city and Al-Kut city.Clinically, 60 sample among 80 were gave positive results depending on Nugent score and Amsel criteria ,the Bacteriologicall test showed the percentages of gram negative bacteria (E.coli ,K.pneumoniae, P.mirabilis, Ps.aeruginosaand A. baumanniiwere) were (38.3 ,28.3, 26.6,20,16.6,15)% respectively, while, the percentages of gram positive bacteria ( Lactobacillus spp., S. epidermidis , S. aureus, S. agalactiae and S. faecaliswere( 100, 46.6, 38.3,18.3 ,11.6)% respectively.The results of molecular detection revealed that the specific primers amplified in 48 sample of vaginal swabs and produced a single band with a molecular weight of 210 bp for G. vaginalisgene, and 9 samples of vaginal swabs for Leptotrichia/Sneathia gene and produced a single band with a molecular weight of 320bp,3While negative results for other bacteria such as Atopobiumvaginae and Bacterial Vagionosis Associated Bacteria 1,2,3 ( BVAB1, BVAB2 and BVAB3) .The results of LactobacillusSpp., showed that among 60 samples of LactobacillusSpp., 28 isolates (46.66%) were L. acidophilus and the PCR product appeared as a single DNA band with a molecular weight of 192bp,while 32 isolates (53.33%) were L. fermentum,the PCR product appeared as single DNA band with a molecular weight of 600 bp. Sequencing of 16s rRNA of G.vaginalisand L.fermentumwasagreed with PCR identification give similar identity in percentages (87.5 and 100)% respectively with the standard strains in NCBI web site. While for Leptotrichia spp. it differs and related to modified nucleic acid bacteria in comparison with NCBI web site and hence is considered as a novel BV associated bacteria in vagina.